The Importance Of Outdoor Education As A Strategy For Language Exploration, Experimentation, And Development Among Students In The Arabic Language Proficiency Diploma For Non-native Speakers At Ksu. - Djemai Mahmoud Boulaares (The Journal of Studies in Language, Culture and Society, 2025)
This study explores the impact of outdoor education as an innovative approach to enhancing Arabic language skills among non-native speakers enrolled in the Arabic Language Proficiency Diploma program at King Saud University. By extending learning beyond the traditional classroom, outdoor education immerses students in real-world contexts, fostering cultural engagement and facilitating practical language use. This paper presents a comprehensive analysis of the benefits of outdoor education, its practical applications, and the challenges it may present. The effectiveness of this approach was assessed using a structured methodology. The findings reveal that outdoor education significantly improves linguistic fluency, cultural competence, and vocabulary acquisition, providing a valuable alternative to conventional language instruction.